Odpowiedzi

Najlepsza Odpowiedź!
2009-12-19T22:48:56+01:00
Zad.6
a)
(a+2)²+(2a-3)²=a²+2*2*a+2²+4a²-2*2a*3+3²=a²+4a+4+4a²-12a+9=
=5a²-8a+13

b)
(3-x)²+ (x +4)²=3²-2*3*x+x²+x²+2*x*4+4²=9-6x+2x²+8x+16=
=2x²+2x+25

c)
(x+2)²-(3x-1)²=x²+2*x*2+2²-(9x²-2*3x*1+1²)=x²+4x+4-9x²+6x-1=
=-8x²+10x+3

d)
(3x-5)²-(2x-4)²=9x²-2*3x*5+5²-(4x²-2*2x*4+4²)=
=9x²-30x+25-4x²+16x-16=5x²-14x+9

Zad.7
a)
(x-1)²=x²
x²-2x+1=x² /-x²
-2x+1=0 /-1
-2x=-1 /:(-2)
x=½
spr.
(½-1)²=(½)²
(-½)²=(½)²
¼=¼

b)
3x+(6x+1)²=4(5+9x²)-4
3x+36x²+12x+1=20+36x²-4
36x²+15x+1=36x²+16 /-36x²
15x+1=16 /-1
15x=15 /:15
x=1
spr.
3*1+(6*1+1)²=4(5+9*1²)-4
3+(6+1)²=4(5+9)-4
3+7²=4*14-4
3+49=56-4
52=52

c)
(-3x+6)²-2=3x(3x-11)+31
9x²-36x+36-2=9x²-33x+31
9x²-36x+34=9x²-33x+31 /-9x²
-36x+34=-33x+31 /+33x
-3x+34=31 /-34
-3x=-3 /:(-3)
x=1
spr.
(-3*1+6)²-2=3*1(3*1-11)+31
(-3+6)²-2=3(3-11)+31
3²-2=3(-8)+31
9-2=-24+31
7=7

d)
(-6x+2)²=-3(4-12x²)
36x²-24x+4=-12+36x² /-36x²
-24x+4=-12 /-4
-24x=-16 /:(-24)
x=⅔
spr.
(-6*⅔+2)²=-3(4-12*(⅔)²)
(-2*2+2)²=-3(4-12*⁴/₉)
(-4+2)²=-3(4-¹⁶/₃)
(-2)²=-12+16
4=4